ASSESSMENT THE EFFECT OF SEX ON SELECTED MORPHOMETRIC MEASUREMENTS AND SLAUGHTER YIELDS OF AFRICAN CATFISH (CLARIAS GARIEPINUS BURCHELL, 1822): African catfish - Chwastowska-Siwiecka, Iwona (Polish Journal of Natural Sciences, 2023)
This study was aimed at analyzing results of morphometric measurements and slaughter yield of carcass of African catfish depending on gender. The experimental material included 60 fish, with a gender ratio of 1:1 (females ♂ : males ♀), cultured in the intensive system (pond culture). The all fish were fed manually (every 3 h) with pelleted feed prepared at the farm. Morphometric measurements (body weight, total length, body length, side length of the head, head height, the smallest and the largest height of the body and body width) were performed in live fish, whereas post mortem determinations were carried out for contents of particular elements of carcass (head, viscera, fins, skin, bones and fillets). Results achieved demonstrated that male fish were characterized by greater body length, side length of the head and body height compared to females. They were also characterized by higher body weight, yield of carcass and fillets without skin, and by higher contents of head, fins and bones in the total body weight. The statistical analysis showed effect of gender on morphometric measurements and the selected parts of body of catfish.